Energy loss straggling for α-particles in varying thicknesses of Al, Ti and Ni metallic foils. (January 2015) - Kumar, Sunil; Diwan, P.K.; Kumar, Shyam
Abstract: The energy loss straggling for α-particles, in the fractional energy loss limits (Δ E / E )~10–75%, has been measured in varying thicknesses of Aluminum, Titanium and Nickel metallic foils. These measured values have been compared with the corresponding computed values adopting different theoretical/semi-empirical formulations viz. Bohr, Lindhard and Scharff, Bethe–Livingston, Yang et al. and Titeica. The purpose of this comparison is to recognize the best formulation for such straggling calculations. Highlights: Straggling in energy loss for 5.486 MeV α-particles in three metallic foils was measured. For α-particles, 241 Am source was used. Measured straggling values were compared with the commonly used straggling formulations. Titeica theory was recognized as a best theory.